Report : Community Network Forum - Community Health and Social Services Network (CHSSN) (2015)
Community organizations carry out their missions in an environment of continual reorganization of the health and social services system. In this context, groups must face the challenge of mobilizing resources to engage communities in a collective effort to commit the public system to meet the specific needs of community members. Groups are also challenged to introduce innovative approaches into their programs in a continual effort to achieve positive and long-lasting results.

Annual Report : 2014-2015 - Réseau de l’est de l’île pour les services en anglais (REISA) (2015)